Austria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper focuses on the medium-term budgetary framework (MTBF) for Austria. Austria is part of a trend among many countries to consider some form of MTBF. This paper describes the proposed framework in Austria and assesses it in light of the experience of other countries. The general conclusion is that the track records are mixed, but that, on balance, the experiences with MTBFs have been favorable. The paper also examines the long-term fiscal challenges arising from demographic change.